The Relationship Obesity And Coronary Heart Disease Incident: Hubungan Antara Obesitas Dengan Kejadian Penyakit Jantung Koroner Di Poli Jantung Rs Islam Jakarta Cempaka Putih - Gibran, Muhammad Syahryan; Nurulhuda, Uun (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Coronary Heart Disease (CHD) is a type of heart disease caused by a lack of blood flow to the heart. One of the riskfactors for CHD is obesity. Patients with obesity have lipid levels that can cause atherosclerosis. In previous studies,there were differences of opinion regarding the relationship between obesity and the incidence of CHD, namely that therewas no relationship between obesity and the incidence of CHD. The purpose of this study was to determine whether thereis a relationship between obesity and the incidence of CHD. The research method used is quantitative with a case controlapproach. The sample in this study were 170 respondents who were treated at the heart polyclinic at the Jakarta IslamicHospital Cempaka Putih using a consecutive sampling technique. The samples were measured for height and weight forobesity, as well as interviews regarding age, gender, family history of CHD, smoking history. The diagnosis of CHD inrespondents was determined by looking at medical records. The results showed that there was a relationship betweenobesity and the incidence of CHD with a P value = 0.012. The conclusion of this study is that there is a relationshipbetween obesity and the incidence of CHD in patients at the Jakarta Islamic Hospital Cempaka Putih Polyclinic.Recommendations for further research are expected to be able to examine the relationship between other risk factors forCHD and CHD incidence.